Ljudje na poziv - Pušnik, Maruša (Javnost (Ljubljana), 2007)
The article presents a cultural-historical study of telephone uses in Sloveniain the twentieth century. Telephone is considered a cultural product, a social institution, and a technical apparatus. The article discusses broad consequences of the development of telephone, social context of the expansion of this communication technology, and different roles telephone had in the development from the first wire-line prototypes to the massive use of mobile phone. By presenting life-stories and recollections of phone uses in Slovenia,the author seeks to analyse the "telephone culture". She discusses the importance of telephone for the every-day life of people after the telephones have "invaded" private houses and individuals' intimate worlds and thus re-defined the relationship between private and public communication, which echoed in the transformation of every-day habits, patterns of social interaction and sociability, and reorganisation of the society at large.
Keywords: communication; komuniciranje; medosebne komunikacije; telefonija; javnost; vsakdanje življenje; sociologija kulture